Contextual validation of HEMLEM tool used for measuring clinical micro-learning environments - Khizar Ansar Malik; Ayesha Fahim; Abeer Anjum; Saira Khalid; Shafaq Malik; Ahsan Sethi (PLoS ONE, 2025)
Objective A positive clinical learning environment is essential for the professional development of medical and dental students. The Healthcare Education Micro Learning Environment Measure (HEMLEM) was originally developed in the UK but lacked cross-cultural validation, limiting its global applicability. This study aims to adapt and validate a revised version of HEMLEM (HEMLEM 2.0) in Pakistani medical and dental schools, with a focus on factorial structure, measurement invariance, and psychometric robustness. Methodology The HEMLEM was culturally adapted and validated for content and face validity through expert assessments and pilot testing to evaluate Pakistani medical and dental institution’s micro-learning environment. A subsequent cross-sectional study was conducted to evaluate the tool’s construct validity and reliability using a sample population. Data was collected using a revised 12-item HEMLEM instrument administered via Google Forms. Descriptive statistics, including skewness and kurtosis, were calculated. Confirmatory Factor Analysis (CFA) was used to compare one-factor, three-factor, and bifactor models. Measurement invariance was tested across gender and academic discipline (MBBS/BDS) using multi-group CFA. Internal consistency was evaluated using Cronbach’s alpha and McDonald’s omega. Results A 20-expert panel assessed the content validity of HEMLEM tool, with an I-CVI score above 0.78 for each item and UA-CVI at 0.8. Ten items were revised based on feedback, forming HEMLEM 2.0. Construct validity was evaluated through responses from 628 Pakistani medical and dental students. The three-factor model of HEMLEM 2.0, comprising “Supervision,” “Autonomy,” and “Atmosphere,” demonstrated good fit (CFI = 0.932, RMSEA = 0.081) and was preferred over the bifactor model due to theoretical parsimony. Full configural, metric, and scalar invariances were confirmed across both gender and discipline. Item-level skewness and kurtosis indicated acceptable normality. Reliability testing showed Cronbach’s Alpha of 0.897, Omega coefficient of 0.929, and composite reliability of 0.901, indicating strong internal consistency. Conclusion HEMLEM 2.0 is a culturally adapted, psychometrically robust tool for assessing the clinical micro-learning environment in Pakistani healthcare education. Its strong validity and reliability support its use for quality improvement, curriculum evaluation, and educational research. Future studies should examine test-retest reliability, specialty-specific insights, and applicability in other low- and middle-income countries.